An Unusual Case of Eosinophilia with Systemic Lupus Erythematosus: A Case Report and Review of Literature. (28th February 2022) - Mishra, Aman; Kuikel, Sandip; Rauniyar, Robin; Poudel, Sagar; Thapa, Sital; Pathak, Nibesh; Rimal, Suman; Pandey, Kundan Raj; Jha, Saket
Abstract : Eosinophilia can be caused by various conditions, parasitic infection being the most common cause. Here, we present a case of a 17-year male who presented with multisystem involvement and eosinophilia. He was later diagnosed to have systemic lupus erythematosus with eosinophilia which is a rare combination. Despite being a diagnostic challenge, these patients can be well managed with immunosuppressive therapy if recognized in time.